Implementasi Metode PID Untuk Pengaturan Kecepatan Motor DC Pada Mesin Pencacah Bunga Rosella Kering Untuk Pengolahan Teh Rosella - Delila Cahya Permatasari; Nara Agata Abiwindraya; Wahyu Dirgantara; Nachrowie Nachrowie (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2022)
In Indonesia Rosella Flowers are used as herbal tea. The process of brewing Rosella Tea is brew 3 – 4 dried rosella petals with 200ml hot water. This brewing process takes a long time from 10 minute or 15 minute. One of way to improved is crushing the rosella flower to little shape with apply PID method. This machine use Atmega32 as controller, speed sensor, laser sensor, and DC Motor as actuator. The working principle of this machine is to stabilize DC motor speed, effective procces is at 900 RPM, in this speed takes 07 minutes 15 seconds to finished the process, and laser sensor has not detected rosella flower to crushing the system will turn off automatically. With percentage overshoot 10.2 %, settling time 245 seconds, and biggest error of speed sensor is 2.6 % . The reuslt from speed sensor will display at LCD 2*16 to make easily to analysis.